2020
DOI: 10.3390/ijerph17186751
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Quality of Life in Patients with Age-Related Macular Degeneration by Using Filters

Abstract: Background: Age-related macular degeneration (AMD) is a disease with an increasing incidence due to the general aging of the population that decreases the patient’s quality of life. This work aims to study whether selective cut optical filters improve the AMD patient’s quality of life. Methods: Prospective and longitudinal study in 79 patients. Visual acuity, contrast sensitivity, and the line differences in the Colenbrander test were measured. Patients answered The National Eye Institute 25-Item Visual Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…An unanticipated finding in this study was that none of the participants elected to obtain a coloured tint in their near-reading spectacles to match their preferred colour filter settings in the LuxIQ/2 (usually light yellow or similar to an FL-41 tint), since they ultimately preferred white light for reading. There is conflicting evidence in the literature regarding the impact of coloured filters on near functioning, as some previous studies have shown improvements in average reading speed or the ability to perform near activities with coloured filters in patients with age-related macular degeneration, 5,15 while another study did not demonstrate beneficial effects. 5 Considering the findings of the present study, it may be suggested that clinical providers should inquire about patients' preferences for white light versus a light yellow or FL-41 coloured tint for near reading, with the expectation that a task light may be sufficient and more desirable by most visually impaired individuals.…”
Section: Discussionmentioning
confidence: 98%
“…An unanticipated finding in this study was that none of the participants elected to obtain a coloured tint in their near-reading spectacles to match their preferred colour filter settings in the LuxIQ/2 (usually light yellow or similar to an FL-41 tint), since they ultimately preferred white light for reading. There is conflicting evidence in the literature regarding the impact of coloured filters on near functioning, as some previous studies have shown improvements in average reading speed or the ability to perform near activities with coloured filters in patients with age-related macular degeneration, 5,15 while another study did not demonstrate beneficial effects. 5 Considering the findings of the present study, it may be suggested that clinical providers should inquire about patients' preferences for white light versus a light yellow or FL-41 coloured tint for near reading, with the expectation that a task light may be sufficient and more desirable by most visually impaired individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Visual rehabilitation methods will positively affect not only the patient's visual functions but also their psychosocial status [ 20 ]. Caballe-Fontanet et al detected statistically significant increases in general vision, near and distance activities, ocular pain, color vision, vision-specific mental health, role difficulties, and dependency subscale scores in the NEI-VFQ-25 using only filter glasses in 79 patients with nonexudative ARMD [ 21 ]. In our study, 45.6% of the patients in the rehabilitation group preferred the 450 nm filter glasses in addition to low vision aids for near and distance.…”
Section: Discussionmentioning
confidence: 99%
“…Caballe-Fontanet et al (2020) detected statistically signi cant increases in general vision, near and distance activities, ocular pain, color vision, vision-speci c mental health, role di culties, and dependency subscale scores in the NEI-VFQ-25 using only lter glasses in 79 patients with nonexudative ARMD [20]. In our study, 45.6% of the patients in the rehabilitation group preferred the 450 nm lter glasses in addition to low-vision aids for near and distance.…”
Section: Künzel Et Al (2020) Performed Ophthalmic Examinations Includ...mentioning
confidence: 99%